Manajemen Guru Sebagai Sumber Daya Manusia di Sekolah - Meitriyani, Meitriyani; Hariri, Hasan (9 772338317006, 2023)
Abstract: Teacher Management as Human Resources in Schools. The purpose of writing this article is that the writer wants to analyze what procedures need to be carried out in implementing teacher management as human resources in schools. The low quality of teachers and the quality of education in schools makes human resource management (MSDM) necessary for every educational institution. The research used by the author is descriptive research using the Systematic Literature Review (SLR) method of descriptive review. The data used in this study is secondary data derived from national scientific articles in the range of 2017 to 2022. The database used is Google Scholar. The keywords used are teachers, human resource management, procedures, schools. The writer identified 67 articles and selected 25 of them for analysis. The results of the literature study found 11 articles that match the criteria and objectives of this study. The results of this study are: human resource management procedures in schools that can be applied, namely: program planning, recruitment and selection, teacher placement, training and development, teacher performance evaluation or assessment, and compensation.Keywords: teacher, human resource management, schoolDOI: 10.23960/jmmp .v11.i1.2023.02